PERANAN PASTA KULIT MANGGIS DALAM PEMBENTUKAN JARINGAN IKAT KOLAGEN PADA PROSES KESEMBUHAN ULKUS MUKOSA MULUT - Lanny Sunarjo; Irma Haida Yuliana Siregar; Supriyana Supriyana (Jurnal Kesehatan Gigi, 2019)
Prevalence of mouth ulcer in patients who visited dental clinic ranged 27%, contributing factors as chemical trauma and infection. Topical medicine available on the market today contained some chemicals might be contraindicated in hipersensitive patient, required an alternative medication of herbal ingredients that had same efficacy, safe and no allergic. Several studies had shown that xanthone contained in rind mangosteen could act as an anti inflammatory, anti bacterial and anti alergic. Aim of this study was to investigate application of rind mangosteen paste towards collagen formation in mouth ulcer healing due to chemical and infection. The experimental research with post test control group design, randomly obtained a total sample of male Wistar rats was 24 and divided into 4 groups @ 6 tails where 2 (two) treatment groups (due to chemical and infection) smeared with mangosteen rind paste and 2 (two) other treatment groups smeared with standard medicine (PVP), then from each group decapitated the 3rd, 7th and 10th day. Observation was carried out macroscopically and microscopically then the data obtained on the 10th day performed Kruskal Wallis test. The result of this study showed time healing for chemical ulcer was 9 days (standard medicine) and 10 days (mangosteen rind paste) while infectious ulcer was 10 days (standard medicine) and 9 days (mangosteen rind paste). Role of mangosteen rind paste proved significant in formation collagen of infectious ulcer, usage of standar medicine decreased area of collagen formation on 3rd, 7th and 10th day (0,133 mm; 0,083 mm; 0,059 mm) while usage of mangosteen rind paste might increase this collagen formation (0,073 mm; 0,083 mm; 0,115 mm). There was significant difference broad of collagen formation with p value = 0,016. Topical usage of mangosteen rind paste might accelerate mouth ulcer healing and increase formation of collagen in infectious mouth ulcer.